The BTS ARMY Help Center Movement as a Non State Actor in Supporting the Sustainable Mental Health Agenda in 2018-2021 - Putri, Karenina Mutiara; Kresnawati, Megahnanda Alidyan (Universitas Muhammadiyah Ponorogo, 2023)
This study aims to find out what efforts have been driven by the ARMY Help Center to encourage changes in the stigma of BTS or ARMY fanaticism that has grown in society. BTS's first win at an international music award event made many people hate BTS. This has an impact on BTS fans, namely ARMY. ARMY felt a lot of blasphemy from BTS haters because they considered cheating in BTS' winning results. The worsening condition of the ARMY's mental health led one ARMY to form a social movement organization with a focus on improving mental health, namely the ARMY Help Center. With the same identity, a collective identity is formed to voice the importance of mental health. Their agenda has helped ARMY and people in need, such as holding mental health help services, social media campaigns, conducting webinars, discussions, and conferences on mental health, and writing and publishing books related to mental health. This research is descriptive and qualitative in nature. For data collection techniques using interview methods and data through written sources, for example, notes, transcripts, books, newspapers, reports, and others. The results of the study show that the agenda that the ARMY Help Center is carrying out can also indirectly break the bad stigma that a K-pop fan is not all fanatical and exaggerated. As a non-state actor, you can create a positive social movement and can help many people who need mental health assistance.